Information Technology for Classification of Donosological and Pathological States Using the Ensemble of Data Mining Methods - Kryvova, O.A.; Kozak, L.M. (Cybernetics and computer engineering, 2021)
The purpose of the paper is to develop information technology for the classification of human health states using an set of Data Mining methods and to carry out its validation on examples of a operators` functional state and patient's disease severity. Results. The developed IT unites several stages: I — data pre-processing; II — clustering, selecting the homogeneous groups (data segmentation); III — predictors` identification; IV — classifying the studied states, development of predictive models using machine learning algorithms (Decision trees, Support vector machines, neural networks) and the method crossvalidation. The proposed IT was used to classify the operators` functional statе and the patients` severity in case of disease progression. Метою роботи є розроблення інформаційної технології класифікації стану здоров'я людини за допомогою комплексу методів Data Mining за об'єктивними та експертними характеристиками. Результати. Розроблена інформаційна технологія об'єднує кілька етапів: I — попереднє оброблення даних; II — кластеризація, вибір однорідних груп (сегментація даних); III — ідентифікація предикторів; IV — класифікація досліджуваних станів, розроблення прогнозних моделей за допомогою алгоритмів машинного навчання (дерев рішень (Decision trees, опорних векторних машин Support vector machine, нейронних мереж) та методу перевірки навчальної вибірки (cross-validation). Запропоновану ІТ використано для дослідження функційного стану операторів та класифікації тяжкості стану пацієнтів у разі прогресування захворювання.